Nilai-Nilai Religi dan Filosofis Tari Tor-Tor Pada Pernikahan Adat Mandailing Natal (Studi di Desa Huta Pungkut) - Sahriyani Dewi; Muhammad Muhammad; Ismet Sari (UIN Sumatera Utara, 2022)
Mandailing Natal Regency or often also referred to as Madina is one of the regencies in North Sumatra. In Madina there are several villages, one of which is Huta Pungkut village. Mandailing Natal, especially the village of Huta Pungkut, has a variety of unique customs and cultures that are different from other regions. Among them are crafts, Bagas Godang, lubuk larangan, and arts, including dance. The art of dance is an ancestral heritage that we must protect and preserve, the hope is that it will not be recognized by other nations. One of the Mandailing Natal cultural customs is the tor-tor dance. This study uses a qualitative method, which aims to determine the procession of the tor-tor dance and find out what the religious and philosophical values of the tor-tor dance are at the Mandailing Natal traditional wedding. The purpose of this research was carried out because many people, including the next generation of Mandailing Natal, did not know the meaning of the tor-tor dance. The results of this study are that in the tor-tor dance starting from the elements of movement, rhythm, movement and poetry there are religious and philosophical values, namely praise and gratitude to Allah, advice from parents to children, commendable morals, love for family, developing attitudes mutual help, happiness in life in this world and the hereafter and prayers for safety. The messages of Islamic communication in these tor-tor movements are to protect, ask for and receive luck, respect, honor the elders, protect the family with love, joy, mutual support and help.